2012
DOI: 10.1371/journal.pone.0034192
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination of CXCR7 Controls Receptor Trafficking

Abstract: The chemokine receptor CXCR7 binds CXCL11 and CXCL12 with high affinity, chemokines that were previously thought to bind exclusively to CXCR4 and CXCR3, respectively. Expression of CXCR7 has been associated with cardiac development as well as with tumor growth and progression. Despite having all the canonical features of G protein-coupled receptors (GPCRs), the signalling pathways following CXCR7 activation remain controversial, since unlike typical chemokine receptors, CXCR7 fails to activate Gαi-proteins. CX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
89
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 53 publications
11
89
2
Order By: Relevance
“…Our finding that the CXCR4 C terminus shows strong constitutive phosphorylation when fused to CXCR7 points to the possibility that the CXCR7 protein prefers a conformation that attracts G protein-coupled receptor kinases. Indeed, conversion of all C-terminal serine and threonine residues into alanines eliminates ␤-arrestin recruitment and impairs CXCR7 trafficking (37). These findings are supported by our results showing that CXCR7-mediated CXCL12 uptake and CXCL12 degradation are slower with the CXCR7-ST/A mutant.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our finding that the CXCR4 C terminus shows strong constitutive phosphorylation when fused to CXCR7 points to the possibility that the CXCR7 protein prefers a conformation that attracts G protein-coupled receptor kinases. Indeed, conversion of all C-terminal serine and threonine residues into alanines eliminates ␤-arrestin recruitment and impairs CXCR7 trafficking (37). These findings are supported by our results showing that CXCR7-mediated CXCL12 uptake and CXCL12 degradation are slower with the CXCR7-ST/A mutant.…”
Section: Discussionsupporting
confidence: 83%
“…Thus, the CXCR7 C-terminal domain accelerates not only ligand-independent receptor internalization but also ligand-independent receptor degradation. Given that CXCR7 is ubiquitinated at lysine residues in the C terminus (37) and that the rapid loss of total and surface CXCR7 receptors during cycloheximide exposure were attenuated in our CXCR7-K/R mutant, it seems likely that C-terminal ubiquitination reduces stability of the CXCR7 protein.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…7B) suggested that some M 1 mAChRs might be targeted to the late endosomes/lysosomes. We, therefore, investigated the extent of receptor degradation after different ligand combinations using a whole cell anti-myc ELISA on permeabilized cells, which allowed us to detect total receptors (32). Although the total amount of receptors was not affected after incubation with CCh or BQCA alone followed by ligand washout, a significant decrease was observed after washout of CCh and BQCA as well as when BQCA was maintained in the recovery media (Fig.…”
Section: Effects Of Bqca On Endocytic Trafficking Of the M 1 Machr-mentioning
confidence: 99%
“…Ubiquitination of the platelet-activating factor receptor occurs at steady state, and it is not modulated by agonist stimulation, but seems to regulate receptor degradation after agonist stimulation (Dupré et al, 2003). In contrast, CXCR7 is basally ubiquitinated, but, upon agonist stimulation, becomes deubiquitinated in a process that requires receptor phosphorylation and ␤-arrestin recruitment (Canals et al, 2012). It is noteworthy that ubiquitination of CXCR7 is restored upon removal of ligand, resulting in recycling of internalized receptor back to the cell surface.…”
Section: Dores and Trejomentioning
confidence: 99%